Iranian Expert Opinion about Necessary Criteria for Hospitals Management Performance Assessments - Elham Dadgar; Ali Janati; Jafar Sadegh Tabrizi; Mohammad Asghari-Jafarabadi; Omid Barati (Tabriz University of Medical Sciences, 2012)
Background: Managers in the hospital should have enough managerial skill to be coordinated with the complex environment. Defining a competency framework assessment for hospital man-agement will help to establish core competencies for hospital managers. The aim of this study was to develop concrete and suitable performance assessment criteria using expert's view.Methods: In this qualitative study in total, 20 professionals participated in the interview and Fo-cus Group Discussions (FGD). Two of informants were interviewed and 18 professionals par-ticipants in three focus group discussions. Discussions and interviews were well planned, the FGD environments were suitable and after interviews completion the notes were checked with participant for completeness. Thematic analysis method was used for the analysis of qualitative data.Results: Findings from 3 FGDs and 2 semi structured interviews done with 20 professionals were categorized accordance to themes. The findings were classified in 7 major and 41 sub themes. The major themes include competency related to planning, organization and staff per-formance management, leadership, information management, and clinical governance and per-formance indicators.Conclusion: All participants had hospital administration experience; so their explanation impor-tant in identifying the criteria and developing hospital managers' performance assessment tool. In addition to professional perspectives and studies done in other countries, in order to design this kind of tools, it is necessary to adopt the obtained findings to the local hospital conditions.